A Diagnostic-Oriented Screening Scale for Anxiety Disorders: The Center for Epidemiologic Studies Anxiety Scale (CESA) - André Faro; André Faro; William W. Eaton (Frontiers in Psychology, 2020)
ObjectivesThis paper introduces a new diagnostically oriented screening scale for anxiety disorders, the Center for Epidemiologic Studies Anxiety scale (CESA), designed in parallel to the revised Center for Epidemiologic Studies Depression scale (CESD-R). In this study, the CESA was used as a diagnostic screening tool for detecting the presence of anxiety disorder symptomatology ascertained by a clinical psychiatric evaluation based on the DSM-5 criteria. The CESA is designed to provide an overall evaluation of anxiety as well as to screen for four important anxiety disorders (agoraphobia, social phobia, blood-illness phobia, and panic disorder).MethodsThe test sample was composed of 80 adults seeking treatment for mental problems in a general psychiatric clinic. We assessed the receiver operating characteristic (ROC) curve of the CESA in comparison to the psychiatric interview.ResultsThe main findings suggest that the CESA is useful for screening for anxiety in general (alpha coefficient of 0.83), as well as for the four common anxiety disorders. The criterion validation confirmed a high level of compatibility between the CESA and the psychiatric evaluation.ConclusionThis is the initial report regarding the CESA and future research will focus on specific aspects of criterion validity for each disorder.